Aluminum extraction with nitrogen-containing phenolic extractants - Ya. Yu. Ershova; E. I. Lysakova; V. I. Bukin; M. V. Tsygankova; A. M. Reznik (Тонкие химические технологии, 2015)
Liquid extraction is a promising method of aluminum extraction from potassium bittern (mother liquors) solutions. Extractants are nitrogen containing chelating phenol type compounds, namely: N-(2-hydroxy-5-nonylbenzyl)-β,β-dihydroxyethylamine (NBEA-0) and N-(2-hydroxy- 5-nonylbenzyl)-β-hydroxyethylmethylamine (NBEA-2) dissolved in a mixture containing 75% vol. of octane + 25% of octanol. The most effective extraction parameters are as follows: extraction time 15 min, contamination of K2CO3 350 grams per liter, alkali concentration 4.5 M, concentration of the extractants more than 0.3 M. Under given conditions metal: extractant ratio is 1:1. The back-extraction was presumed to be performed using 3.5 М alkaline solutions. It was determined that results obtained when NBEA-0 was used as an extractant are insignificantly better in comparison with using NBEA-2.